2015
DOI: 10.1074/jbc.m115.689604
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Molecular Architecture of the Phosphoinositide 3-Kinase p85α Homodimer

Abstract: Background:The class IA PI 3-kinase regulatory subunit p85␣ dimerizes by mechanisms not fully understood. Results: p85␣ dimerization is driven by intermolecular interactions at both its N and C termini. A structural model of the p85␣ dimer reveals conformational diversity. Conclusion: p85␣ dimerization is poised to link the heterologous assemblies that regulate PI3K signaling. Significance: The p85␣ dimer is a dynamic participant in PI3K signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“…Our analysis using purified p85α and PTEN proteins showed that the p85α-I177N mutant retained its ability to both bind and regulate PTEN, similar to that of wild type p85α. This is in contrast to the proposed role for the I177 residue within the BH–BH dimer interface noted in the crystallized protein 29 , but was in good agreement with a recent study suggesting that in solution BH domains do not typically interact 44 . Cheung et al .…”
Section: Discussionsupporting
confidence: 89%
“…Our analysis using purified p85α and PTEN proteins showed that the p85α-I177N mutant retained its ability to both bind and regulate PTEN, similar to that of wild type p85α. This is in contrast to the proposed role for the I177 residue within the BH–BH dimer interface noted in the crystallized protein 29 , but was in good agreement with a recent study suggesting that in solution BH domains do not typically interact 44 . Cheung et al .…”
Section: Discussionsupporting
confidence: 89%
“…We have shown that ACK inhibits degradation of the p85α isoform, which would lead to an excess of regulatory subunits over catalytic subunits. p110free p85α exists (24) and can form homodimers (39). The formation of both p110-free monomeric p85 and dimeric p85 would be promoted by elevated levels of p85.…”
Section: Discussionmentioning
confidence: 99%
“…The integrative structure modeling protocol ( i.e ., stages 2, 3, and 4) was scripted using the Python Modeling Interface (PMI) package, version 4d97507, a library for modeling macromolecular complexes based on our open-source Integrative Modeling Platform (IMP) package 98 , version 2.6 (https://integrativemodeling.org). The current procedure is an updated version of previously described protocols 66,72,90,101104 . Files containing the input data, scripts, and output results are available at https://salilab.org/npc2018.…”
Section: Methodsmentioning
confidence: 99%
“…The remainders of the Nup sequences not in rigid bodies (36.8% of residues, excluding FG repeats) were represented as flexible strings of beads. In a rigid-body, the beads have their relative distances constrained during configurational sampling, whereas in a flexible string, the beads are restrained by the sequence connectivity, excluded volume, and potentially additional restraints, such as chemical cross-links, as exemplified in our previous studies 43,66,72,101,117 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation